Fierce, free, and full of fire : the guide to being glorious you - Hatmaker, Jen (Nelson Books, an imprint of Thomas Nelson, 2020)
No more hiding or people-pleasing up in here, sisters. No more being sidelined in your own life. It is time for us to be brave, to claim our gifts and quirks and emotions. You are set free and set up and set on fire.